2017
DOI: 10.1002/2327-6924.12489
|View full text |Cite
|
Sign up to set email alerts
|

Key considerations for moving to a nurse faculty role

Abstract: Expert nurse practitioners (NPs) grounded in clinical practice are needed to prepare the future NPs. This article discusses key considerations for moving from the role of expert clinician to nurse educator. The considerations for making the move to the educator role including reflection on rewards associated with teaching, similarities between practice and education, faculty support, and role responsibilities are presented from a dean's perspective. The typical hiring process is discussed including what questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The NNEs in the current study reported the need for newly recruited nurse educators to be properly orientated to the nurse educator role before they commence full teaching roles. According to Marfell et al ( 2017 ), orientation is an educative experience intended to support NNEs to begin their new roles, usually in a formal workshop format. Earlier studies have reported that orientating NNEs before they begin teaching is vital to easing the transition (Dempsey, 2007 ; Gilbert & Womack, 2012 ; Mann & De Gagne, 2017 ; Mower, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NNEs in the current study reported the need for newly recruited nurse educators to be properly orientated to the nurse educator role before they commence full teaching roles. According to Marfell et al ( 2017 ), orientation is an educative experience intended to support NNEs to begin their new roles, usually in a formal workshop format. Earlier studies have reported that orientating NNEs before they begin teaching is vital to easing the transition (Dempsey, 2007 ; Gilbert & Womack, 2012 ; Mann & De Gagne, 2017 ; Mower, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complexity of the nurse educator role, experienced nurse clinicians who choose to transition to the novice nurse educator (NNE) role ought to be adequately prepared with the requisite pedagogical knowledge, attitudes and skills to make the transition easier and successful (Booth et al, 2016 ; Marfell et al, 2017 ; Smith et al, 2019 ). However, international studies have revealed that not all NNEs recruited into Health Training Institutions (HTIs) are adequately prepared and they often struggle to transition into their new educator role (Brown & Sorrell, 2017 ; Cooley & De Gagne, 2016 ; Grassley & Lambe, 2015 ; Miner, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deans and academic leaders have published perspectives regarding skills and topics important to successful transitions of clinicians to faculty roles (Marfell et al, 2017). They point out similarities and differences in clinical and academic work activities and schedules and identify characteristics and skills of the NP who is likely to adapt well to academia.…”
Section: Review Of Literaturementioning
confidence: 99%
“…To lay groundwork for future promotion, they recommend that new faculty take the time early in their teaching appointment, to create a curriculum vita and portfolio that documents their performance in teaching, scholarship, and service. The authors also suggest that new NP faculty should be socialized to academic culture and its language, learn about teaching and student evaluation strategies, and understand curriculum development and accreditation (Marfell et al, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Making a transition from clinical nursing practice to academic nursing implies making a counterintuitive coming back to a beginner from proficient because having high proficiency in clinical nursing practice does not guarantee proficiency in the nursing academic role; therefore, taking the decision to transition from bedside to classroom requires cautious consideration of many private and professional factors [ 7 ]. The choice to pursue a role in academic nursing must prompt the clinical nurse to take a personal account and evaluate one’s personal desired place of work and set of skills [ 8 ]. Therefore, to ensure nurses in the clinical setting are making the transition from the clinician to educator role for the correct reasons, expert nurse clinicians should reflect on what is motivating their decision to transition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%